Endo-N-acetylneuraminidase associated with bacteriophage particles. - Kwiatkowski, B (1982)
A bacteriophage (phi 1.2) has been isolated for Escherichia coli K235 (O1:K1:H-). phi 1.2 is specific for the host capsular polysaccharide (colominic acid). The phage forms plaques with acapsular halos and thus carries a glycanase activity for colominic acid, a homopolymer of alpha (2 leads to 8)-linked N-acetylneuraminic acid (NeuNAc) residues. Upon incubation with purified phi 1.2 particles, a solution of K1 polysaccharide loses viscosity and consumes increasing amounts of periodate. Also, by gel filtration, the production of colominic oligosaccharides (down to a size of two to three NeuNAc residues) can be demonstrated. No NeuNAc monomers, however, are formed. The capsules of E. coli strains with the K92 antigen, which consists of NeuNAc residues linked by alternating alpha (2 leads to 8) and alpha (2 leads to 9) bonds, are also depolymerized by the phi 1.2 enzyme. Under the electron microscope, phage phi 1.2 is seen to belong to Bradley's morphology group C (D. E. Bradley, Bacteriol. Rev. 31:230-314, 1967); it has an isometric head, carrying a baseplate with six spikes. By analogy to other virus particles with host capsule depolymerase activity, it is probable that the phi 1.2 endo-N-acetylneuraminidase activity is associated with these spikes.